The Role of Visfatin, Leptin, and IL-18 in Polycystic Ovarian Syndrome Patients - Sukayna H. Rashed; Eman A. Hadi (Medical Journal of Babylon)
Background: Several local studies revealed there is a rising occurrence of polycystic ovarian syndrome in the city of Mosul at different ages, even among unmarried females. Objectives: The aim of this study was to investigate the impact of body mass index (BMI) on a range of biochemical markers among PCOS patients and healthy women at Mosul women's clinics and hospitals. Materials and Methods: A total of 26 non-obese women with PCOS who have BMIs ≤ 25 kg/m2, along with 34 obese women with PCOS symptoms were enrolled in this study. Patients with and without IR in PCOS were also classified. Insulin resistance was measured with the help of the homeostatic model index (HOMA-IR). Blood samples were collected during the second and third days of the menstrual cycle. The following biochemical variables were also evaluated: fasting blood sugar, fasting insulin, insulin resistance, leptin, visfatin, and IL-18. Results: The results found that there were 27 cases of PCOS without insulin resistance (HOMA-IR< 2.69) and 33 cases with insulin resistance (HOMA-IR≥2.69). In all the groups included in this study, the findings were statistically evaluated to determine a correlation coefficient between the variables that were assessed with each other and their correlation with the development of the disease condition and the possibility of employing them as a diagnostic indicator. Patients with PCOS had significantly elevated serum IL-18 and visfatin levels but normal leptin concentrations. Conclusion: The study suggests that leptin acts locally in the follicle and that visfatin may play a role in most cases. Insulin resistance can be found in this particular group of patients. However, for the time being, it is unclear if it will be recognized as a true adipocytokine associated with the pathophysiology of PCOS. In PCOS women, elevated levels of IL-18 were associated with insulin resistance and BMI.